Recurrent condylar luxation after third molar extraction: an uncommon condition treated by eminectomy - Maiolino Thomaz Fonseca OLIVEIRA; Átila Roberto RODRIGUES; Flaviana Soares ROCHA; Darceny ZANETTA-BARBOSA
INTRODUCTION: Extraction of third molars can rarely provoke post-operative complications, such as temporomandibular joint disorders (TMDs). OBJECTIVE: Although the literature presents a series of discussions of the clinical evidence related to this subject, in this report, we present an uncommon case of a patient submitted for the extraction of third molars who presented, in postoperative monitoring, with recurrent bilateral condylar luxation. CONCLUSION: Due to this critical condition, the patient was successfully treated by bilateral eminectomy.